Pengaruh Transfer Pricing dan Profitabilitas Terhadap Tax Avoidance Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014 - 2018 - Elsera Stephanie; Kuncu Saragih; Emerald G. M Tobing (Buletin Ekonomi, 2023)
The purpose of this study is to find out how the effect of transfer pricing and profitability on tax avoidance. The data used in this study is secondary data with quantitative analysis techniques. The population in this study consisted of 178 manufacturing companies listed on the Indonesia Stock Exchange for a five-year period, from 2014 to 2018. The sample in the study used was purposive sampling. Data processing was carried out using the SPSS version 25 program. Keywords: Transfer Pricing, Profitability, Tax Avoidance